Potato Consumption and Risk of Colorectal Cancer in the Norwegian Women and Cancer Cohort. (19th May 2017) - Åsli, Lene A.; Olsen, Anja; Braaten, Tonje; Lund, Eiliv; Skeie, Guri
ABSTRACT: Potatoes are the fourth most plentiful food crop in the world, yet the scientific literature on the health effects of potato consumption is scarce. This study aimed to investigate the association between potato consumption and the risk of colorectal cancer (CRC) among 79, 778 women aged 41–70, in the Norwegian Women and Cancer study. Information on diet, lifestyle, and health was collected by questionnaire. CRC cases ( n = 912) were identified through registry linkage. Adjusted Cox proportional hazard models were used to estimate the association between potato consumption and the risk of CRC. Results showed that high potato consumption was associated with a higher risk of CRC (hazard ratio [HR]: 1.32, 95% confidence interval [CI]: 1.10, 1.60 for ≥3 potatoes per day versus 0–7 potatoes per week). The same association was found for rectal cancer (HR: 1.68, 95% CI: 1.19, 2.36), and same tendencies were found for colon cancer (HR: 1.20, 95% CI: 0.96, 1.50). When stratified by body mass index (BMI) (<25 and ≥25 kg/m 2 ), significant associations were found with BMI <25 kg/m 2 for CRC (HR: 1.48, 95% CI: 1.15, 1.89) and rectal cancer (HR: 1.95, 95% CI: 1.25, 3.06). No significant interaction between potato consumption and BMI ( P = 0.49) was found.